A review on windows incorporating water-based liquids. (15th January 2021) - Piffer, Yuri; Lamberts, Roberto; Ordenes Mizgier, Martin; Güths, Saulo
Abstract: This paper presents a review of windows filled of water-based liquids which absorbs solar radiation and will be referred to herein as water-based windows (WBWs). These liquids have spectrally-selective and high thermal capacity properties for optical and thermal performance improvement. A WBW relates to windows that features transparent, semi-transparent, colorless or colored visual performance. Its profile consists of liquid layers inside clear or solar control multilayer glazing or tubular structures. A detailed analysis of WBW design differences and performance is carried out and studies were classified according to common characteristics regarding two main categories: WBW without and with fluid exchange. Optical and thermal methodologies are evaluated, highlighting the limitations and accomplishments for future researches. A water-filled WBW can transmit more light compared to the same glazing when empty. It can also perform substantially better than many commercially available glazing products, in terms of either promoting solar heat gain or reducing cooling demand. There was a predominance of cases with better heating performance for WBWs without fluid exchange. On the other hand, most cases of WBWs with fluid exchange where better for cooling performance if the circulating fluid was not preheated. Also, water heated in WBWs can be applied in the building facilities.